2021
DOI: 10.3390/curroncol28030210
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Landscape of Lower Grade Glioma Based on Age-Related Non-Silent Somatic Mutations

Abstract: Glioma accounts for 80% of all malignant brain tumours and is the most common adult primary brain tumour. Age is an important factor affecting the development of cancer, as somatic mutations accumulate with age. Here, we aimed to analyse the significance of age-dependent non-silent somatic mutations in glioma prognosis. Histological tumour grade depends on age at diagnosis in patients with IDH1, TP53, ATRX, and EGFR mutations. Age of patients with wild-type IDH1 and EGFR increased with increase in tumour grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Moreover, we observed that patients with TP53 positive tumors were more likely to be diagnosed with cancer at a younger age than patients with wild-type TP53 tumors, as expected (47). Interestingly, PTEN mutations were mutually exclusive with IDH1 mutations and wild-type TP53 tumors were presented in IDH1 wild-type tumors only (14,26,48).…”
Section: Idh1 Mutation Pten Mutation Tp53 Mutationsupporting
confidence: 83%
“…Moreover, we observed that patients with TP53 positive tumors were more likely to be diagnosed with cancer at a younger age than patients with wild-type TP53 tumors, as expected (47). Interestingly, PTEN mutations were mutually exclusive with IDH1 mutations and wild-type TP53 tumors were presented in IDH1 wild-type tumors only (14,26,48).…”
Section: Idh1 Mutation Pten Mutation Tp53 Mutationsupporting
confidence: 83%
“…The robust deterministic process of single-cell cancer induction that we uncovered suggests that the aberrant reactivation of Epi-Driver genes involved in reprogramming/pluripotency (such as VENTX/NANOG, POU5/OCT4) might be relevant to the irreversible malignant transformation of a cell. Reprogramming Epi-Drivers are important regulators of cell viability, survival and proliferation in several cellular contexts, from embryonic stem cells to cancer cells [22][23][24][25][26][27] . Due to their capacity to modulate epigenetic memory and cell plasticity, these reprogramming factors may drive the early stages of malignant transformation in vivo once (re)activated aberrantly.…”
Section: Discussionmentioning
confidence: 99%
“…Here using an optogenetic approach we permanently turn on an oncogene (KRASG12V) in a single cell of a zebrafish brain that, only in synergy with the transient co-activation of a reprogramming factor (VENTX/NANOG/OCT4), undergoes a deterministic malignant transition and robustly and reproducibly develops within 6 days into a full-blown tumor. The controlled way in which a single cell can thus be manipulated to give rise to cancer lends support to the "ground state theory of cancer initiation" through "short-range dispersal" of the first malignant cells preceding tumor growth.Recently, it has been shown that genes involved in embryonic development, pluri/multipotency and cell reprogramming such as VENTX/NANOG and POU5/OCT4 are abnormally reactivated in late cancer stages, where acting as Epigenetic Drivers (Epi-Drivers) they empower cancer cells with Cancer Stem Cell (CSCs) features, resistance to anti-cancer therapies and potential for cancer recurrence/relapse 21,22,23,24,25,26,27 . Although it is evident that such Epi-Drivers confer a selective advantage to CSCs in a full-blown cancer, whether they play a role during the early phases of malignant transformation is still unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several mutation-driver genes (Mut-driver-genes) have been characterized in cancer cells so far (e.g., KRAS , BRAF , MYC , TP53 ), however vsDPGs have gained attention in the process of carcinogenesis due to their tumorigenic potential [ 145 , 146 , 147 ]. VENTX and NANOG were found highly expressed in brain (glioma/glioblastoma) [ 148 , 149 , 150 ], pancreatic [ 151 , 152 , 153 ] renal [ 154 , 155 ], esophageal [ 156 , 157 ] and testicular cancers [ 28 , 158 , 159 ]. Interestingly, VENTX and NANOG share activity in hematopoiesis by repressing the genes responsible for terminal differentiation (e.g., TAL1 , KLF1 ) [ 160 , 161 ], as well as promoting leukemia [ 161 , 162 , 163 ].…”
Section: Developmental Potential Guardians In Human Diseasesmentioning
confidence: 99%